HUBUNGAN KUALITAS TIDUR DENGAN PENINGKATAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Nazmi, Annisa Nur; Nisa, Elly Khoirun; Masroni, Masroni; Indriani, Ninis (Universitas Pesantren Tinggi Darul Ulum, 2024)
Sleep quality is a condition that shows an individual's ability to sleep and get the amount of rest according to their needs. Someone with poor sleep quality has a 4.1 times greater risk of developing hypertension compared to someone who has good sleep quality. This study aims to determine the relationship between sleep quality and increased blood pressure in hypertensive patients. This research uses a quantitative, cross-sectional approach. The sample for this research was 52 people using accidental sampling technique. Statistical analysis used Spearman's rho test. The instrument uses the Pittsburgh Sleep Quality Index (PSQI) questionnaire and aneroid blood pressure monitor and stethoscope. This study showed that almost half were in the grade 2 hypertension category with poor sleep quality, 17 respondents (33%). The results of the Spearman's rho test show that there is a relationship between sleep quality and increased blood pressure in hypertensive patients with a value of p = 0.026. The correlation value obtained was 0.308 in a positive direction with low relationship closeness. It is hoped that hypertension sufferers will be able to maintain a healthy lifestyle and maintain good quality sleep so that blood pressure does not increase. Keywords: Sleep Quality, Blood Pressure, Hypertension